Analysis of Supply Chain Management Against Operations of PT Benih Citra Asia - Allief Mardika; Dessy Isfianadewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
PT Benih Citra Asia is a company that operates in industry in agriculture, in particular industry seeds of food and horticultural crops which are the result of plant breeding (Plant Breeding). This research aims to analyze the effect of implementation of Supply Chain Management (SCM) on the operations of PT Benih Citra Asia. This research uses qualitative methods by conducting in-depth interviews and direct observation as data collection techniques. The research results show that implementation of Supply Chain Management at PT Benih Citra Asia has had a significant positive impact on the company's operational efficiency. Supply Chain Management helps optimize the flow of goods and information throughout the supply chain, which contributes to smooth production processes and responsiveness to market changes. Good collaboration between departments, especially between the Plant and IT divisions, is very important to ensure that product information is always up to date and accurate. Apart from that, this research also found that raw material inventory management that is difficult to predict and fluctuations in customer demand are the main challenges in Supply Chain Management. To overcome this problem, closer collaboration with suppliers and customers is required as well as the use of advanced information technology to improve visibility and coordination between departments. Overall, this research confirms that Supply Chain Management is a key factor in improving the efficiency and operations of PT Benih Citra Asia. Cross-departmental collaboration and effective communication are critical elements in successful implementation of Supply Chain Management.